Produksi serbuk limbah cangkang tiram di Gampong Alue Naga untuk meningkatkan nilai ekonomis dan mengurangi dampak lingkungan (Production of oyster shell waste in Alue Naga Village to increase economic value and reduce environmental impact) - Puspita, Kana; Herliana, Fitria; Amalia, Zahra; Nazar, Muhammad; Izzaty, Nur; Fadlia, Faradilla (Universitas Syiah Kuala, 2023)
Alue Naga Village in Banda Aceh City is a village that has a river and is directly adjacent to the sea, so this village has the potential to produce oysters. Oyster shell waste is usually dumped on the banks of the river, into the river, or thrown back into the oyster farm. This results in land and water pollution. This pollution can cause rivers to become shallow; if this continues, it can result in natural disasters such as floods. Therefore, Therefore, this service aims to provide education and training related to oyster shell waste into something more valuable. This activity also involved CV. Natural Aceh Food is a forum for the community to market its products. The production process required 5 minutes to grind 8 kilos of oyster shells and produce 7.7 kilos of oyster shell powder. Overall, the specific target achieved from this service activity is the packaged oyster shell powder to reduce oyster waste and empower the female oyster farmers in Alue Naga Village to earn additionalincome.